Copper(I)-mediated and microwave-assisted Caryl-O carboxylic coupling: Synthesis of benzopyranones and isolamellarin alkaloids - Nopporn Thasana (2018)
(Chemical Equation Presented) A simple and highly effective C-O carboxylic coupling reaction catalyzed by copper(I) salts has been developed to synthesize benzopyranones. The reaction of various 2-halobiarylcarboxylic acids was examined using microwave irradiation. A new class of pyrroloisoquinoline alkaloid, isolamellarin, was synthesized based on the annulation of dihydroisoquinoline with aryl pyruvates under basic condition and Cu-mediated/MW-assisted C-Ocarboxylic lactonization. © 2007 American Chemical Society.